Does top management team responsible leadership help employees go green? The role of green human resource management and environmental felt‐responsibility. (8th March 2022) - Lu, Hui; Xu, Weiting; Cai, Shaohan; Yang, Fang; Chen, Qingqing
Abstract: Drawing on social information processing theory, the current study investigates the relationship between top management team (TMT) responsible leadership and employee organizational citizenship behavior for the environment (OCBE) from a vertical perspective, and whether green human resource management (GHRM) and employee environmental felt‐responsibility can play a sequential mediating role between them. Totally, 102 middle‐level managers and 527 employees in 102 Chinese teams voluntarily participated in our study. Drawing on above data, our study verifies that TMT responsible leadership was positively associated with both GHRM and employee environmental felt‐responsibility. In addition, GHRM mediated the positive effects of TMT responsible leadership and employee environmental felt‐responsibility. Also, GHRM can further promote employee OCBE through employee environmental felt‐responsibility. Overall, the positive relationship between TMT responsible leadership and employee OCBE was sequentially mediated by GHRM and employee environmental felt‐responsibility. Therefore, the current study shows the way to achieve corporate environmental sustainability strategy.